Mastite bovina sob nanocontrole: a própolis nanoestruturada como nova perspectiva de tratamento para rebanhos leiteiros orgânicos - Troncarelli, Marcela Zampoli [UNESP] (2013)
Organic dairy farms are supposed to use only phytotherapeutical and homeaopatical actives for mastitis control in cows. However, there are a low number of actives available for this application. Considering the bactericide action of the propolis and the fact that this substance is allowed in organic dairy farms, Brazilian researches developed the nanoestructured propolis, a promissor poduct for intramamary treatment against mastitis. It is expected that this nanostructure presents better antimicrobial effects and lower irritability for mammary glands, considering that the previous in vitro studies done against bacterial reference strains showed excellent results. In vivo studies are being conducted to evaluate the safety and efficacy of a nanostructured propolis formulation in dairy organic farms. If the expectations regarding the safety and efficacy of the nanostructured propolis be confirmed, betimes the final formulation may be directed for industrial production, especially attending the demands of dairy farms organic systems.